Potential and actual evapotranspiration and Landsat derived indices - P. Kumar; D. Deka; A. Yadav; Ashwani .; M. Kumar; J.P. Das; A. Singh; A. Gurjar (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Evapotranspiration is an important component of water balance associated with the hydrological cycle and biological processes. Accurately estimating the rate of evapotranspiration is crucial for understanding fluctuations in water availability and effectively managing water resources in a sustainable manner. The study aims to examine the correlation between actual evapotranspiration and potential evapotranspiration by assessing the linkages with vegetation and snow cover in an ecologically fragile located in the northwestern Himalaya.MATERIALS AND METHODS: The present study uses remote sensing Landsat satellite data series to map vegetation cover and snow cover in the area. Remote sensing data accessed from Moderate Resolution Imaging Radiometer evapotranspiration project data was used for calculating evapotranspiration and potential evaporation. The data from the Climatic Research Unit (2000–2022) was additionally utilized for the computation of potential evapotranspiration. The study investigates variances in evapotranspiration and explores correlations between normalized difference vegetation index and normalized difference snow index. It further examines the correlation between potential evapotranspiration and actual evapotranspiration.FINDINGS: The study conducted from 1991 to 2021 demonstrates a notable rise in vegetation cover by 20.18 percent, showcasing spatial variations across the region. Conversely, there has been a significant decline in the extent of snow cover throughout this period. A positive correlation was identified between vegetation cover and evapotranspiration, whereas a negative correlation was observed between snow cover and evapotranspiration. Actual evapotranspiration is on the rise while potential evapotranspiration is declining throughout the region.CONCLUSION: Hydrological cycle of a region is governed by many factors such as climate (precipitation, temperature), geohydrology, land use and land cover, socio-economic condition of habitants and institutions. Vegetation cover, snow cover, actual evapotranspiration and potential evapotranspiration and their relationship indicates changes in local and regional climate. An incremental rise in plant growth across the study site, coupled with spatial variability and a reduction in snow cover in the elevated mountainous zone, is influencing both actual evapotranspiration and potential evapotranspiration. Increase in actual evapotranspiration in the High Himalayan area of Himachal Pradesh attribute to substantial increase in vegetation cover in the dry cold desert region. The findings of the study will contribute to the comprehension of essential elements of water cycles and water budgets, facilitating improved resource allocation for climate-resilient sustainable initiatives.